INTERNALISASI NILAI KARAKTER KEWIRAUSAHAAN PADA ANAK USIA DINI MELALUI TEKNIK ROLE PLAYING - Hasmawaty Hasmawaty Hasmawaty; Syamsuardi Syamsuardi Syamsuardi; Nurul Jamiah Sidiq; Delvhina Manga (Jurnal Panrita, 2026)
Entrepreneurship education from an early age plays an important role in shaping the character and basic skills that children need to face the challenges of life in the digital and globalised era. Through entrepreneurship education, children are taught not only to be consumers, but also creators and leaders. One effective approach in teaching entrepreneurship is the role playing technique, which allows children to actively learn in situations that simulate entrepreneurial activities. This technique not only improves social and emotional skills, but also prepares children to adapt to change and create their own opportunities. This research aims to explore how role playing can internalise the value of entrepreneurship in early childhood, as well as its impact on children's character development. Through a group business simulation at PAUD Doa Ibu, children were involved in the roles of managers, waiters, and buyers in a children's cafe business. The results showed that children developed skills in teamwork, creativity, leadership, decision-making, responsibility, and risk-taking. This study concludes that the role playing technique is effective in internalising entrepreneurial values in early childhood, which can be applied in formal and informal education to prepare an independent and future-ready young generation.